The Development of Grade 6 Students’ Thai Literature Skills through Inquiry-Based Learning and Mind Mapping - Muenyong, Warisa; Pengpoom, Brapaas (Ratchaphruek Journal, 2024)
This research studied the development of grade 6 students' Thai literature skills through inquiry-based learning and mind mapping. The purposes of this research were: 1) to develop a Thai literature learning plan for grade 6 students, 2) to compare learning achievement between pre-learning and post-learning, and 3) to study students' level of satisfaction towards learning through the learning plan. The sample consisted of 28 grade 6 students from Anubanwangsaipoon School during the second semester of the 2023 academic year, selected by simple random sampling. The research instruments were: 1) the Thai literature learning plan, 2) achievement tests for Thai literature learning, and 3) a questionnaire measuring student satisfaction. The statistical analyses utilized included mean, standard deviation, and t-test dependent. The research results indicated that: 1) the results of considering the consistency and appropriateness of the elements in the learning plan yielded significantly high results ( = 4.45, S.D. = 0.04), and 2) pre- and post-learning tests showed average scores of 10.75 and 24.54 respectively, and when comparing scores before and after studying, it was found that the students' post-test scores were significantly higher than pre-test scores (p < .05), and 3) the students' level of satisfaction was at a high level ( = 4.48, S.D. = 0.12).